Otimização bioeconômica do regime de manejo para Eucalyptus grandis W. Hill no estado do Rio Grande do Sul - Marangon, Gabriel Paes (2015)
The goal of this study is to develop Density Management Diagrams for Eucalyptus grandis W. Hill, which will serve as auxiliary models to establish the variation of appropriate density, and the management group, to conduct settlements with the economic evaluation of management employees schemes. To study area were used stands in full density in reduced spacing, located in Rio-grandense Eastern center and Porto Alegre metropolitan in Rio Grande do Su states mesoregions. Of the density models tested, Tang showed good accuracy, with adjusted coefficient of determination of 0,74 and 3,17% coefficient of variation, which served as the base model for determining the population density rates, competition areas, construction of Management Density Diagrams and the size of the average diameter at the time that starts self-thinning for trees planted per hectare density. It was shown that the value of the slope calculated for the model of Tang, was different from that proposed by the author, worth -3/2 of self-thinning law. It was observed that the average diameter size at the time of the start self-thinning occurs with the removal of the population individuals varies considerably with the tree planting density. Preferably, you should lead the development trajectory of the density of trees per hectare below the line of maximum density, where the line of imminent mortality occurs. With reference to the standard diameter of 25 cm was obtained 5 Settlement density index curves describing curves between them proportional exponentially decreasing trends of frequency individuals per hectare with the diameter increment. Management density diagrams with the variables mean diameter, basal area, volume stand density index provided good volumetric estimates per hectare in relation to actual volumes with efficiency of 0,95, indicating good precision. The tested probability distributions, the Weibull function 2 parameters described accurately the frequency of diameters in time, and the re-estimation of its parameters, allowed frequency distributions by diameter class and therefore real development of the stand. The selected trunk shape function was to Hradetzky with determination coefficient of 0,98 and 8.43% coefficient of variation, generating through its integration the estimated volume of the whole stem and parts of it. The Net Present Value of R$ 12.372,35 ha-1 was determined for the management regime with three thinning, at 52,8; 85,4; 121,8 months and last cut at 185,1, higher than the other simulated systems. The Equivalent Annual Value was good and viable economically for all tested systems, the most attractive was the regime where there were two thinnings to 52,8; 85,4 months and last cut at 121,8 months with Equivalent Annual Value of R$1.550,78 ha-1. The internal rate of return was attractive in any of the simulated management regimes, ranging from 6,48% by year in stands without thinning and final cut at 52,8 months at 25,31% by year in stands managed with thinnings at 52,8; 85,4 months and last cut at 121,8 months. The biggest reason benefit on costs was 3.15, obtained in the management regime with two thinning, at 52,8; 85,4 months and last cut at 121,8 confirming the Equivalent Annual Value and Internal rate or return criteria.